Calculation Methods in Heart Rate Variability - Gasmi, Amin (Discontinuity, Nonlinearity, and Complexity, 2026)
A healthy human body depicts variability to a large extent that can be easily described by using statistical algorithms. If this fluctuation arises occur in normal cycle of the heartbeat, it is called as heart rate variability (HRV). The rhythms of a normal and healthy heart continue to change every second with the metabolic activity that provides the heart and brain a new chance for changing and maintaining homeostasis according to variability. The aim of this research is to study long-term, short-term, and very short-term regulations of the body to cope with the condition of the heart as HRV changes. Time domain, frequency domain, non –linear dynamics are being overviewed. Where time-domain shows HRV changes during a time period of three minutes to one hour, frequency domain parameters illustrate the variation of data over an extended period of time. Nonlinear dynamics provides quantitative measurement of probability and biasedness in values obtained from the electrocardiograph. After careful investigation, it became clear as fact that short term i.e., mechanisms which are as less as five minutes and long term that are about one day cannot be correlated and can’t be changed into one another. Moreover, the use of these statistical mechanics in clinical laboratories and therapeutics against myocardial infarction, blood pressure, and diabetes are elucidated in detail to gain access to potential generated by them during heart rate (HR) analysis to control morbidity rate effectively.